101 dog tricks : step-by-step activities to engage, challenge, and bond with your dog - Sundance, Kyra (Quarry Books, 2007)
Performers Kyra and Chalcy illustrate each trick. Trick training is a great way to bond with your dog, help your dog integrate into your family, and keep him mentally and physically challenged. Includes: beg, bow, say your prayers, fetch the paper, find the remote, and more; also, step-by-step instructions to guide the trainer; troubleshooting tips to solve problems; and "build-on" ideas that encourage taking a mastered skill to the next level.--Publisher's description.